481 Best-evidence synthesis: Effectiveness of child drowning prevention interventions. (20th November 2022) - Ashraf, Lamisa; Zia, Nukhba; Agrawal, Priyanka; Green, Abigail; Vincenten, Joanne; MacKay, Morag; Bachani, Abdulgafoor M
Abstract : Background: Globally, drowning is a leading cause of death among children aged 1–4 years, followed by children 5–9 years of age. While several drowning prevention strategies have been introduced over the years, a synthesis of evidence of effective interventions is lacking. The purpose of this study was to synthesize evidence on the effectiveness of existing drowning prevention interventions. Methods: A stepwise approach to gathering evidence on child injury prevention interventions was undertaken with reviews of (1) systematic reviews published between 2008 and 2020, (2) primary studies published between 2020 and 2021, and (3) hand searched articles on drowning prevention. The study population of interest was children under 20 years of age. Results: Drowning prevention interventions can be grouped into 3 categories: education, engineering measures, and legislation and enforcement. Education on water safety practices did not result in effective uptake of safe practices at homes, in high-income countries ((OR 1.21, 95% CI 0.85 to 1.72)). Globally, swimming lessons and adult supervision were found to be most effective in preventing drowning deaths in children under 14 and under 5, respectively. Engineering measures such as pool fencing prevents about 50% of swimming pool drownings in young children but it needs to be supplemented with other interventions like adult supervision and legislation and enforcement. Conclusion: Effective drowning prevention strategies are necessary to reduce the burden of child drowning while simultaneously addressing the sustainable development goal of reducing child mortality rates. Further research and evaluation of packages of interventions combining education, engineering and enforcement are required.